Ожиріння у вагітних – патогенетичний фактор ризику порушень гепатобіліарної системи - Тарасенко, К.В.; Громова, А.М. (Таврический медико-биологический вестник, 2011)
Цель исследования – изучить взаимосвязь инсулинорезистентности у беременных женщин на
фоне ожирения І, ІІ, ІІІ степени с показателями гепатобилиарной системы. Снижение чувствительности
к инсулину у беременных женщин на фоне ожирения проявляется как на системном уровне, так и на
уровне гепатоцитов, о чём свидетельствует гипертриглицеридемия и повышение активности
мембраносвязанного фермента гамма-глутамилтранспептидазы. The main purpose of the investigation is a study of the relationship of pregnant women.s insulin resistance
with obesity against indicators of hepatobiliary system. The existence of obesity and the reduction of sensitivity
to insulin in pregnant women occur at the systemic level and also have influence on hepatocytes. The
evidence of this may be seen in the increasing activity of the membrane-bound enzyme . gamma-
glutamyltranspeptidase and hypertriglyceridemia.